PENGARUH IKLAN TELEVISI MEDIA MASSA TERHADAP PERILAKU KONSUMTIF MASYARAKAT DESA SARI GALUH KECAMATAN TAPUNG KABUPATEN KAMPAR KIRI PEKANBARU - Oktri Permata Lani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Advertising today has become the most widely encountered anywhere in the mass media, and also has many fans. Advertising has become a media mainstay for producers to introduce their products and promote their products. Because it is undeniable that many ads can hypnotize audiences. Basically, advertising is a form of mass communication used by advertisers to deliver messages or information to the public through a particular medium (Suhandang, 2005). The messages contained in the ad had a remarkable influence on audiences to trigger the consumption of the product. Until the end of the product, not consciously aware of, has become part of consumers' lives. Television has become a part of a modern society that functions other than as a disseminator of information and entertainment, as well as a promotional tool products most powerful in herding the public mind the target audience is, to enter the trap through television advertising until in the end the audience was willing to spend pocket, just to follow what is being offered through a series of fantastic images that have been constructed meaning. Ads are part of the promotional mix, which is part of the 4Ps in the marketing mix of products that place, price and promotion. For advertising, promotion strategy serves as the main tool in creating awareness of the products and the state of mind of potential customers to take good purchasing decisions.Keywords : Advertsing, Television, Consumptive Behaviour